Radiation observation at Asuka Station, Antarctica and radiative properties of the atmosphere and snow surface - Teruo Aoki (National Institute of Polar Research, 1997)
Radiation observations at Asuka Station (71°31′S, 24°08′E, 930m), Antarctica in 1988 are summarized and the radiation budget at Asuka is compared with those at other stations. The diurnal variations of net radiation due to cloud condition at Asuka are 20W/m^2 for shortwave, 40-60W/m^2 for longwave and 20-60W/m^2 for total radiation. Cloud have a large effect on the radiation budget mainly through longwave radiation. The magnitude of this effect is approximately equal to the amplitude of the seasonal variation and differences among the stations in Antarctica. On the other hand, snow albedo is simulated with a multiple scattering model for the atmosphere-snow system. The result is that the spectral albedo of snow depends on the snow grain size, solar zenith angle, cloud condition and structure of snow layers. It is shown that near infrared wavelengths are effective for remote sensing of the snow physical parameters and discrimination between the snow surface and clouds from space.